Pemberdayaan UMKM dengan TikTok Ads: Pendekatan Pemasaran Digital pada Central Bedug di Desa Lebak Mekar, Kabupaten Cirebon - Whydiantoro; Abdul Kholiq (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
UMKM (Usaha Mikro, Kecil, dan Menengah) plays a crucial role in the Indonesian economy, especially in rural areas. However, many UMKM face challenges in marketing, technology, and business management. Central Bedug, a UMKM engaged in bedug craftsmanship in Lebak Mekar Village, struggles to effectively promote its products. To address these issues, a Kuliah Kerja Nyata (KKN) focused on entrepreneurship was implemented to provide training to craftsmen on using TikTok Ads as a digital marketing strategy. This study uses a qualitative method with an exploratory descriptive approach to examine the craftsmen's understanding of TikTok Ads and its application in promoting their products. The results show that the training successfully enhanced the craftsmen's knowledge of digital marketing and equipped them with skills to create engaging ads on TikTok. The craftsmen also felt more confident and independent in marketing their products using TikTok Ads. This training also demonstrated the great potential of TikTok Ads in empowering UMKM, particularly in rural areas, to expand their market reach and improve the competitiveness of local products. Thus, TikTok Ads can be an effective tool for UMKM to introduce their products to a wider audience at a more affordable cost.